Corrigendum: POPIA Code of Conduct for Research - Rachel Adams (South African Journal of Science, 2021)
Jerome Amir Singh's affiliation was erroneously given as: Centre for Medical Ethics and Law, Stellenbosch University, Stellenbosch, South Africa. The correct affiliation is: School of Law, Howard College, University of KwaZulu-Natal, Durban, South Africa.